Managing crisis communication by tourism actors in the new normal era at the beaches of Yogyakarta - Yani Tri Wijayanti; Handini Handini; Maya Sandra Rosita Dewi; Rahmah Attaymini (Universitas Negeri Yogyakarta, 2022)
Yogyakarta is one of the destinations in Indonesia affected by the Covid-19. Currently, tourist objects in Yogyakarta are gradually starting to open to the public, and one of them is beach tourism, although it can lead to a new cluster risk of the spread of Covid-19. According to the Texas Medical Association, traveling to a beach is included in a moderate risk with a score of 5-6, and health protocols are still required. Applying the crisis management and crisis communication model of Coombs, J, Holladay, this study analyzes how tourism actors manage crisis communication at the beaches of Yogyakarta in the new normal era. A qualitative case study approach was used to illustrate that crisis communication management is an effort to manage a crisis to provide solutions to the beach tourism due to the Covid-19. Crisis management consists of stages, for example, pre-crisis, crisis, and post-crisis. Through these stages, tourism actors and tourists can determine steps they must prepare for during the Covid-19 crisis. In order to resolve the crisis during the pandemic, it is necessary to adopt new habits by tourism actors and tourists. New habits need to be communicated directly or through existing media because communication is essential in crisis resolution.